2014
DOI: 10.1016/j.dental.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Ion release from, and fluoride recharge of a composite with a fluoride-containing bioactive glass

Abstract: Objectives Materials that are capable of releasing ions such as calcium and fluoride, that are necessary for remineralization of dentin and enamel, have been the topic of intensive research for many years. The source of calcium has most often been some form of calcium phosphate, and that for fluoride has been one of several metal fluoride or hexafluorophosphate salts. Fluoride-containing bioactive glass (BAG) prepared by the sol-gel method acts as a single source of both calcium and fluoride ions in aqueous so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 39 publications
3
44
0
1
Order By: Relevance
“…they were equivalent to the control culture without composite). In other work, we have verified that these composite formulations do release calcium and fluoride ions, but apparently they did not contribute significantly to the cell response [38]. Further evidence that the BAG itself was not cytotoxic was apparent when comparing the three different BAG-containing formulations, which showed no statistical difference in cytotoxicity despite the composites having 5, 10 or 15% BAG.…”
Section: Discussionmentioning
confidence: 63%
“…they were equivalent to the control culture without composite). In other work, we have verified that these composite formulations do release calcium and fluoride ions, but apparently they did not contribute significantly to the cell response [38]. Further evidence that the BAG itself was not cytotoxic was apparent when comparing the three different BAG-containing formulations, which showed no statistical difference in cytotoxicity despite the composites having 5, 10 or 15% BAG.…”
Section: Discussionmentioning
confidence: 63%
“…The recharging properties of F-releasing materials were investigated using topical fluoride agents or fluoride-containing toothpastes [44-48]. Glass ionomer cements (GIs), RMGIs, and compomers were shown to release, absorb, and re-release fluoride ions.…”
Section: Discussionmentioning
confidence: 99%
“…The BAG-F filler particle used in the present study had a larger surface area than the BAG filler [6]. This increased surface area for a soluble particle enhances the dissolution rate of ions from the glass [42].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that BAG containing composites showed mechanical properties comparable to commercial composites [2]. Also, adding a filler particle based on a fluoride-containing BAG (BAG-F) enabled the composite to release both calcium and fluoride ions in solution, and to be rechargeable with fluoride upon exposure to external fluoride solutions [6]. While these properties provide optimism about the potential use of BAG additives in composites, the potential dissolution of the glass filler may cause concern about the integrity of the resin composite surface, and its overall esthetic appearance during aging.…”
Section: Introductionmentioning
confidence: 99%